Targeted Delivery of 111In Into the Nuclei of EGFR Overexpressing Cells via Modular Nanotransporters With Anti-EGFR Affibody - Karyagina, Tatiana S.; Ulasov, Alexey V.; Slastnikova, Tatiana A.; Rosenkranz, Andrey A.; Lupanova, Tatiana N.; Khramtsov, Yuri V.; Georgiev, Georgii P.; Sobolev, Alexander S. (Frontiers in Pharmacology, 2020)
Since cell nucleus is one of the most vulnerable compartments, the maximum therapeutic effect from a variety of locally acting agents, such as photosensitizers, alfa-emitters, Auger electron emitters, will be expected when they get there. Therefore, the targeted delivery of these agents into the nuclei of target tumor cells is necessary for their anticancer effects and minimization of side effects. Modular nanotransporters (MNT) are artificial polypeptides comprising several predefined modules that recognize target cell, launching their subsequent internalization, escape from endosomes, and transport the drug load to the nucleus. This technology significantly enhances the cytotoxicity of locally acting drugs in vitro and in vivo. Epidermal growth factor receptors (EGFR) are useful molecular targets as they are overexpressed in glioblastoma, head-and-neck cancer, bladder cancer, and other malignancies. Here, we examined the possibility of using internalizable anti-EGFR affibody as an EGFR-targeting MNT module for drug transport into the cancer cell nuclei. It binds to both murine and human EGFR facilitating preclinical studies. We showed that MNT with affibody on the N-terminus (MNTN-affibody) effectively delivered the Auger electron emitter 111In to target cell nuclei and had pronounced cytotoxic efficacy against EGFR-overexpressing human A431 epidermoid carcinoma cells. Using EGFR-expressing human adenocarcinoma MCF-7 cells, we demonstrated that in contrast to MNT with N-terminal epidermal growth factor (EGF), MNTN-affibody and MNT with EGF on the C-terminus did not stimulate cancer cell proliferation.